The evergreen process hazard analysis: An essential next step. Issue 4 (22nd August 2022) - Olsen, Jody E.
Abstract: The evergreen process hazard analysis (PHA) is an essential next step in hazard identification, risk analysis, and process safety risk management. The evergreen PHA addresses weaknesses in PHA practices that allow the facility PHA to degrade and become out‐of‐date during the periods between 5‐year revalidations. This degradation in the PHA has the potential to elevate safety risk in the facility. This paper outlines prerequisites and initial steps that support moving to evergreen PHA. Initial steps include developing the document flow process, establishing triggering events, and defining the PHA protocol for interim PHA studies. A phased approach for implementing evergreen PHA is outlined. Challenges and barriers, real and perceived, are discussed along with solutions. The implementation of a well‐designed and maintained evergreen PHA process not only supports better awareness of hazards within the facility but also allows for continual improvement of the PHA. Five‐year revalidation efforts may be reimagined and refocused to be more effective and to use resource time more efficiently. These benefits can ultimately contribute to safer and more reliable operations.